Federal Republic of Yugoslavia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper and Statistical Appendix for the Federal Republic of Yugoslavia outlines the progress made in the fiscal area since late 2000, focusing on the overall fiscal adjustment (developments in revenue and expenditure) and reforms of the tax system and social spending. The paper also presents an overview of financial sector reforms in Serbia and Montenegro, elaborates on the closure of the four largest state-owned banks in Serbia, and outlines progress in strengthening prudential supervision in both republics.